Evaluation of the Project “Artvin Bilim ve Robotikle Renkleniyor” from the Viewpoint of Middle School Students (The Eurasia Proceedings of Educational and Social Sciences, 2019)
The aim of this study is to examine how the middle school students participating in the project “Artvin Bilim ve Robotikle Renkleniyor”, which was conducted in Artvin as part of the Scientific and Technological Research Council of Turkey (TÜBİTAK) 4004 Nature Education and Science School program, evaluate the project and the activities in it. In the project, all participants were asked to evaluate the activities with student diaries. Additionally, interviews were conducted with the students on the last day of the project in order to determine their general thoughts on the project and the activities in it. In the study conducted with the qualitative research method, the diaries and end-of-project views of the students were analyzed with content analysis. The data of the study were obtained from a total of 30 students in 6th and 7th grades at six middle schools in Artvin. 19 of the students are female and 11 are male. 14 of these students are in sixth grade and 16 of them are in seventh grade. With the evaluation of the data obtained from the study, the students stated that they found most of the activities informative and fun, that they would like to participate again and that they would recommend the project to their friends. It is seen that students recognize the importance of nature and discover the mutual interaction between nature and science with this project. The students also stated that they liked the learning environment in the project as it made learning enjoyable and that they found it beneficial in terms of enabling them to recognize that active and experiential learning is more permanent. At the end of the analyses, it was observed that the students generally participated in the activities voluntarily and that they had a voluntariness rate of 100% towards the end of the project. Additionally, it was stated that the students aimed to complete the activities on time and were pleased with them.
Keywords: Science school (camp); Middle school student; Student diaries